2T2g ← 1A1g photo-electron spectrum of octahedral tungsten hexacarbonyl. Issue 48 (29th November 2016) - Nikoobakht, Behnam
Abstract : The 2 T2g ← 1 A1g photo-electron spectrum of octahedral tungsten hexacarbonyl W(CO)6 is investigated quantum dynamically. Abstract : The 2 T2g ← 1 A1g photo-electron spectrum of octahedral tungsten hexacarbonyl W(CO)6 is investigated quantum dynamically. The photo-electron spectrum is calculated by construction of a model Hamiltonian in which the T2g ⊗ (2a1g ⊕ 2eg ⊕ 2t2g ) Jahn–Teller (JT) problem up to second-order vibronic coupling (including all possible bilinear terms) together with the spin–orbit (SO) coupling up to the zeroth-order SO splitting is treated. A computational method was suggested to generate all vibronic coupling parameters of the Hamiltonian model and potential energy surfaces (PESs) based on fitting of the minimum eigenvalue of the Hamiltonian model to the adiabatic energies of the energetically lowest branch of the 2 T2g electronic state of W(CO)6 + ˙. This calculation was performed using density functional theory (DFT), and the photo-electron spectrum produced in this way was found to be in good agreement with the experimental results.